RANCANG BANGUN E-COMMERCE SEBAGAI MEDIA PROMOSI DIGITAL DALAM MENUNJANG PENINGKATAN PENJUALAN BERBASIS WEB MOBILE (Pusat Riset dan Inovasi Nasional, 2022)
With so many cosmetic sales, the Grahamode Store is still constrained by 1) the location of stores that are far from urban areas, so that consumers have difficulty making purchases. At this time the sales system used by the Grahamode Shop is that the buyer must come directly to the Shop to make purchases and payments directly. 2) The price of competitive cosmetic products, even relatively cheaper opens up opportunities to compete with similar products in other stores, because the cosmetic products are directly purchased through distributors of each brand. 3) Administration of sales records is still centralized on the computer in the store, so monitoring product sales cannot be done online by the shop owner. 4) A system that is still MS.DOS-based for its operation. Promotions at the Grahamode Shop are also still conventional, namely by distributing brochures, even though it has gone well in Kendal City. The purpose of this study is to produce an information system that can facilitate the Grahamode Shop in conducting promotional activities, and facilitate the process of buying and selling cosmetics online. Data collection methods used are interviews, observations, literature studies, and documentation studies for owners and customers of the Grahamode Store. While the software used is PHP and MySQL as the database. The results of this study produce e-commerce as a mobile web-based promotion and sales media that can help the process of buying and selling products at the Grahamode Shop, and can expand the range of promotions to outside Kendal City.